Population genomics reveals that refugial isolation and habitat change lead to incipient speciation in the Ground tit. (12th March 2019) - Jiang, Zhiyong; Gao, Bin; Lei, Fumin; Qu, Yanhua
Abstract: Complex geological environments and Pleistocene glaciations contribute to speciation. For example, the unique geomorphological configuration and distinct geological evolution of the Qinghai–Tibet Plateau has led to the evolution of many endemic species adapted to a life at the plateau. Most of these endemic birds show no genetic divergence between different populations across the vast plateau region, with one particularly interesting exception. The ground tit ( Pseudopodoces humilis ) exhibits considerable genetic differences between the populations distributed on the central (platform) and those in the eastern margin (edge) of the plateau. Glacial refugial isolation and geographic barrier are hypotheses that have been proposed to explain this unique pattern of divergence. Here we use genome‐wide resequencing data to test these two hypotheses as explanation to the genetic divergence of the ground tit. The neighbor‐joining tree, principal component and STRUCTURE analyses suggest the presence of two incompletely diverged genetic lineages, which are geographically congruent with the populations in the platform and edge areas of the plateau. Our demographic model and population demography analyses estimated that the two populations diverged between 57 and 167 kya, and both populations experienced similar bottlenecks and expansions. Congruently, we also observed retracted suitable habitats for the two populations during the glacial time, suggesting that isolation in different glacial refugia. Interestingly, the genetic divergence between the two populations is further maintained and accumulated by habitat differentiation and morphological divergence. In accordance with this, we observed that highly divergent genomic regions harbour genes enriched in biological functions involved in muscle related processes and metabolic activities. Overall, the separation into different glacial refugia, the habitat difference and the morphological divergence contribute together to the adaptive population diversification in situ and we suggest that the platform and edge populations of the ground tit constitutes an interesting example of incipient speciation.